Literacy Transformation Strategy through Reading Corner Optimization: Pedagogical Analysis and Practical Implementation Grade VIII Students at MTs Miftahul Mubtadiin Banyuwangi - Barata, Mahendra Aswit Sandra; Kurniawan, Nurhafit (Bahasa Indonesia Prima, 2026)
The post-pandemic literacy paradox in Indonesia, characterized by an increase in PISA 2022 rankings amidst a decline in absolute scores, necessitates a reorientation of educational strategies from macro-policy scales toward micro-pedagogical interventions within the classroom. This research presents an in-depth investigation regarding literacy transformation through the optimization of